Optimalisasi Produksi Shovel Komatsu 3000E-6 dengan Metode Overall Equipment Effectiveness (OEE) Pada Pengupasan Lapisan Overburden di Pit 2 Tambang Banko Barat PT. Bukit Asam (Persero) Tbk - Nadia Anggraini Putri; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2018)
Based on production data stripping overburden in West Banko Mine Pit 2 PT. Bukit Asam (Persero) Tbk months of January to August 2017, the production of overburden stripping does not reach the target. This has an impact on the operating costs incurred for stripping each BCM (Bank Cubic Meter) The overburden layer. To determine the potential improvement of a production process and the effectiveness of using a piece of equipment is necessary to do analisis using Overall Equipment Effectiveness (OEE). OEE is known as one of the applications total productive maintenance program that has the ability to clearly identify the root causes and contributing factors that make businesses more focused repairs. Now we know the root of the problem, then use statistical analysis of multiple linear regression to determine the relationship and the maximum limit of barriers - barriers so that production can be achieved. Furthermore fishbone method is used to find the root problems and more detailed evaluation with reference to the results of multiple linear regression statistical analysis acquired. After analysis and repair method - the method of production of shovel komatsu obtained 3000E-6 exceeded what had been planned. But the value of OEE each trencher-load still <85% has not been reached world-class OEE value> 85%, it can be concluded that the state of the equipment is not good. Should be repaired back to standby and tool breakdown.Keywords:  Production, Overall Equipment Effectiveness, Statistical Analysis Multiple Linear Regression, Fishbone Method, Shovel  Komatsu 3000E-6